2019
DOI: 10.1093/geronb/gbz024
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage Between Aging, Migration, and Resilience: Resilience in the Life of Older Turkish and Moroccan Immigrants

Abstract: Objectives Older immigrants are affected by an accumulation of adversities related to migration and aging. This study investigates resilience in older immigrants by examining the resources they use to deal with these adversities in the course of their lives. Methods Data from 23 life-story interviews with Turkish and Moroccan immigrants aged 60–69 years living in the Netherlands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
13
1
Order By: Relevance
“…One other important constraint to be aware of is the fact that our sample is represented by a predominantly highly educated, native-born group of older adults. This may impact the generalizability of our results, as both education level and migration history have been shown to affect (outcome based) resilience among older adults in a number of previous studies ( Lund et al, 2018 ; Klokgieters et al, 2020 ; Szabó et al, 2020 ). Hence, we encourage researchers to perform similar studies to reveal whether the pattern of associations of minority groups approximates the one observed in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…One other important constraint to be aware of is the fact that our sample is represented by a predominantly highly educated, native-born group of older adults. This may impact the generalizability of our results, as both education level and migration history have been shown to affect (outcome based) resilience among older adults in a number of previous studies ( Lund et al, 2018 ; Klokgieters et al, 2020 ; Szabó et al, 2020 ). Hence, we encourage researchers to perform similar studies to reveal whether the pattern of associations of minority groups approximates the one observed in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…The purpose of this study was to explore the relationship between adult attachment, stress-coping, and resilience among first-generation immigrants in the US after controlling for length of stay. Previous studies indicated that education, income, and length of time spent in the US should be considered when measuring resilience (Hartley, 2011; Klokgieters et al, 2020; Schwartz et al, 2019). However, the findings of this present study reveal inconsistent results in that education and income were not correlated with resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have emphasized factors such as an individual’s education (Azmitia et al, 2018; Cavazos et al, 2010), income level (Schwartz et al, 2019), and length of stay (Klokgieters et al, 2020) as possible contributors to resilience. With the immigrant population specifically, the education in a new home country may influence their ability to overcome the various adversities related to the migration process.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Studies of the experiences of loneliness among minority groups are largely country specific, reflecting the migration patterns of specific groups. For example, research in The Netherlands and Germany has been based around the experiences of Turkish, Moroccan and Algerian migrants (see Klokgieters et al 2019 ;2017; Visser and El Fakiriri 2016 ). In our study, we observed a consistent pattern across our different measures with Indian participants reporting the lowest levels of loneliness and Chinese the highest.…”
Section: Discussionmentioning
confidence: 99%